EFFECT OF THE TOXIC LEADERSHIP ON ORGANIZATIONAL PERFORMANCE WITH WORKPLACE DEVIANT BEHAVIOR OF EMPLOYEES AS MEDIATION - Muhammad Rizani; Rahmi Widyanti; Kurniaty Kurniaty; Syahrial Shaddiq; Muhammad Yusri Dzal Yahya (SMBJ: Strategic Management Business Journal, 2022)
Leadership has been an essential topic of organizational science since the beginning of this field. Previously, researchers focused on how successful leaders improve organizations and increase the effectiveness of their followers. This study examines the effect of toxic leadership on organizational performance mediated by work deviant behavior (WDB) of employees with a sample of 100 respondents. The method used in this research is quantitative, in the form of a questionnaire. The results of this study indicate that toxic leadership significantly affects organizational performance, which is significantly less than 0.05. Toxic leadership significantly affects deviant employee behavior, as indicated by a significant value of less than 0.05. Deviant behavior in the workplace has no significant effect on organizational performance with a significantly less than or equal to 0.05. Deviant behavior in the workplace mediates toxic leadership with organizational performance with a direct influence value of 0.734 and an indirect effect of 0.901, so all hypotheses are accepted. This will be an important note for future researchers who will explore and review the causes that deviant behavior in the workplace has no significant effect on organizational performance and deviant behavior in the workplace mediates toxic leadership with organizational performance.